Nitric Oxide restricts iron availability and induces quorum sensing in Streptococcus pyogenes - Ian E. McIntire; Venkatesan Kathiresan; Brian Hoffman; Jennifer Chang; Michael J. Federle; Douglas D. Thomas (Redox Biology)
Nitric oxide (NO) is a free radical signaling molecule with multiple biological functions. As part of the innate immune system, NO has antimicrobial properties playing an important role in host defense. Mechanisms of NO cytotoxicity result from its ability to bind metals and inhibit enzyme function or by increasing nitrosative and oxidative stress within cells. One of the primary biological targets of NO is the chelatable iron pool (CIP) which is quantitatively converted to dinitrosyliron complexes (DNIC) when it reacts with NO. Despite the numerous purported mechanisms attributed to NO's bactericidal properties, DNIC formation and its ability to restrict iron bioavailability from pathogenic bacteria has not been directly tested. Streptococcus pyogenes is a human pathogen that causes a range of diseases spanning from pharyngitis and impetigo to soft tissue necrosis and toxic shock. S. pyogenes employs the Rgg2/Rgg3 quorum sensing (QS) system to regulate aspects of its virulence potential, including biofilm formation, lysozyme resistance, and modulation of host innate immune response. Previous studies found that iron and manganese restriction induced Rgg2/Rgg3 QS, leading us to test whether NO-dependent iron restriction mediated by DNIC formation was sufficient to induce QS and related iron-starvation phenotypes. Here, we demonstrate that DNIC are formed in S. pyogenes exposed to physiologically relevant NO concentrations. The DNIC are formed from the CIP, and formation led to a significant reduction in the CIP, which correlated to a concomitant activation of QS and iron-regulated gene expression. These studies are the first to demonstrate that restriction of iron bioavailability mediated by DNIC formation is a functional mechanism by which NO can regulate QS, gene expression, and cell growth in bacteria.